Cytotoxic and Antimicrobial Flavonoids from Cryptocarya concinna - Huang, Wei; Zhang, Wen-Jing; Cheng, Yi-Qing; Jiang, Rong; Wei, Wei; Chen, Chao-Jun; Wang, Gang; Jiao, Rui-Hua; Tan, Ren-Xiang; Ge, Hui-Ming (Planta Medica, 2014)
Five new flavonoids, cryptoconones A–E (1–5), along with six known compounds (6–11), were isolated from the stems of Cryptocarya concinna. The structures of these compounds were elucidated on the basis of spectroscopic data interpretation, and the absolute configurations were determined via circular dichroism spectra and X-ray crystal analysis. The cytotoxic and antimicrobial activities of these compounds were also evaluated. Compounds 9 and 10 exhibited moderate cytotoxic activities against HCT116, HT-29, SW480, and MDA-MB-231 cell lines with IC50 values ranging from 6.25 to 9.35 µM. Compounds 8 and 11 exhibited antimicrobial activity against Fusarium moniliforme and Botrytis cinerea, respectively, with the same minimum inhibitory concentration of 5 µg/mL.
Keywords: Cryptocarya concinna; Lauraceae; flavonoid; cytotoxic activity; antimicrobial activity